2021
DOI: 10.1186/s12891-021-04941-y
|View full text |Cite
|
Sign up to set email alerts
|

Personal factors associated with carpal tunnel syndrome (CTS): a case-control study

Abstract: Background Carpal tunnel syndrome (CTS) is one of the most common nerve entrapments in the upper limb. In Saudi Arabia, few studies have investigated CTS in the general population. This study aimed to determine the association between personal factors and CTS. Methods A case-control study involved adults aged 18 and above. Cases were recruited from electrophysiology lab records as consecutive case series, while controls were individuals who were fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…The current work showed that, middle aged patients were affected with female sex predominance by CTS. This is in line with previous studies indicated that, CTS affected the middle-aged females [18][19][20][21] .…”
Section: Discussionsupporting
confidence: 94%
“…The current work showed that, middle aged patients were affected with female sex predominance by CTS. This is in line with previous studies indicated that, CTS affected the middle-aged females [18][19][20][21] .…”
Section: Discussionsupporting
confidence: 94%
“…According to the results of the current study, those who have never exercised are 6.23 times more likely to develop carpal tunnel syndrome than people who engage in physical exercise. Such a finding is consistent with the results of studies conducted in Saudi Arabia that showed the odds of having CTS was less than 1 among participants performing physical exercise occasionally (OR=0.11) (27). The result of this study is also supported by the findings of a case-control study conducted in the United States reporting that the odds of having CTS were significantly decreased .…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 91%
“…Our results showed that the higher frequency of repetitive wrist movements was associated with CTS in model 3, according to what has been reported in various studies. [11][12][13] In this regard, a study on Italian workers from meat processing industries showed that prolonged wrist vending was related to an increased CTS diagnosis (adjusted OR = 2.561, 95% CI: 1.10-5.96). [25] Likewise, a study reported that the prevalence of CTS among US dairy parlor workers was 16.6% and 3.6% among non-parlor workers, with a statistically significant difference (adjusted OR = 5.3, 95% CI: 1.1-25.5).…”
Section: Discussionmentioning
confidence: 99%
“…[10] Performing manual tasks that involve repeated flexion, extension, or ulnar deviation of the wrist, vibrations, and mechanical stress on the palmar base increases the risk of CTS. [11][12][13] In this sense, CTS can manifest in both white-collar and blue-collar workers engaged in manual activities, [14] encompassing cooks, cashiers, hairdressers, weavers, musicians, seamstresses, and other workers. [15] The labor aspects associated with the development of STC described above lead us to consider farmers and the activities they carry out as potential triggers for STC.…”
Section: Introductionmentioning
confidence: 99%